Kriteria Pemimpin Perspektif Imam Al-Ghazali Dalam Kitab Ihya’ Ulumuddin - Maharani, Nurma Isfira; Muzakki, Ahmad; Islam, Saiful (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This article was prepared with the aim of examining the criteria for leadership, Imam Al-Ghazali's perspective in the book Ihya' Ulumuddin developed rapidly among pious Salafus. With a deeper understanding of the thinking of the leader, Abu Ḥamid Muḥammad ibn Muḥammad ibn Muḥammad Al-Ghazali Al-Safi'i , also known as Al-Ghazali, an Islamic hujjah (1058–1111 AD), highlighted the substantive component of the usefulness of religious teaching rather than the formal symbolic aspect, bringing together elements that had been separated from the figure of the leader; Leaders must be elected by the people. Imam Al-Ghazali defines an ideal leader as a leader who upholds morality, science and religion. they must also be able to influence the environment in which they operate, heal and prevent destruction in their country or organization, and create a just and prosperous society. The method used is library research, and data analysis using a symbolic interaction approach. It is hoped that the results of this research can explain Imam Al-Ghazali's views regarding leaders in the book Ihya' Ulumuddin.